It only takes one to do many jobs: Amphotericin B as antifungal and immunomodulatory drug - Mesa-Arango, Ana Cecilia; Scorzoni, Liliana; Zaragoza, Oscar (Frontiers in Microbiology, 2012)
“Amphotericin B acts through pore formation at the cell membrane after binding to ergosterol” is an accepted dogma about the action mechanism of this antifungal, and this sentence is widely found in the literature. But after 60 years of investigation, the action mechanism of AmB is not fully elucidated. Amphotericin B is a polyene substance that is one of the most effective drugs for the treatment of fungal and parasite infections. As stated above, the first mechanism of action described was pore formation after binding to the ergosterol present in the membrane. But it has also been demonstrated that AmB induces oxidative damage in the cells. Moreover, amphotericin B modulates the immune system, and this activity has been related to the protective effect of the molecule, but also to its toxicity in the host. This review tries to provide a general overview of the main aspects of this molecule, and highlight the multiple effects that this molecule has on both the fungal and host cells.